2022
DOI: 10.1155/2022/4000024
|View full text |Cite
|
Sign up to set email alerts
|

Does Shanghai International Financial Center Promote RMB Internationalization?

Abstract: The construction of the Shanghai International Financial Center was completed in 2020, which signaled the new age of financial reforms in China. The Shanghai International Financial Center plays a significant part in the progress of RMB internationalization. However, empirical proof of the impacts remains few. So, we conducted an empirical analysis to determine if the Shanghai International Financial Center promoted RMB internationalization effectively. To obtain robust results, we conducted regressions with N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Created in 1990, China's capital market has made tremendous development over the past 30 years, with the SSE, SZSE, and Beijing Stock Exchange (BSE) now (Kathiravan et al 2021). China's capital market has become an integral part of the economic system and aims to building an international financial center (Li and Xu 2022). At the same time, China's capital market needs to consolidate the "barometer" function of economic development unremittingly, continue to deepen two-way opening, effectively enhance the level of capital market opening and steadily improve the multi-level capital market system (Yan and Qi, 2021).…”
Section: Esg Disclosure Regulation For Listed Companies In Chinamentioning
confidence: 99%
“…Created in 1990, China's capital market has made tremendous development over the past 30 years, with the SSE, SZSE, and Beijing Stock Exchange (BSE) now (Kathiravan et al 2021). China's capital market has become an integral part of the economic system and aims to building an international financial center (Li and Xu 2022). At the same time, China's capital market needs to consolidate the "barometer" function of economic development unremittingly, continue to deepen two-way opening, effectively enhance the level of capital market opening and steadily improve the multi-level capital market system (Yan and Qi, 2021).…”
Section: Esg Disclosure Regulation For Listed Companies In Chinamentioning
confidence: 99%
“…Liu (2011) and Hussain et al (2017) used a linear causality test and found significant positive causality between oil price and RMB. More recent studies focus on the impact of RBMI on the international competitiveness of RMB, trade and financing of the belt‐road initiative (Cui et al, 2022; Knoerich, 2021; Li & Xu, 2022; Liang, 2020). Specifically, Wang et al (2021) examined the impact of RMB internationalization and the international situation on China's foreign exchange market as well as the dynamic linkages between the US Dollar/RMB and special drawing right (SDR)/RBM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent studies report inconsistent findings about the potential effect of RMB internationalization on energy prices (Deng & He, 2016; Wen et al, 2017); on petroleum trade (Kamel & Wang, 2019; Kurien & Geoxavier, 2020; Ding et al, 2020); on oil and gas security (Wu, 2014). Accordingly, some studies focused on the international competitiveness of RMB and financing trade in the international markets (Cui et al, 2022; Knoerich, 2020; Li & Xu, 2022; Liang, 2020; Wang et al, 2021). These studies focused more on petroleum prices as affected by RMB internationalization.…”
Section: Introductionmentioning
confidence: 99%